Legal Nullism and Perspectives of Indonesia People's Belief in Today's Legal Conditions - Alvan Rahfiansyah Lubis (Publikasi Indonesia, 2025)
Legal nihilism in Indonesia arises from widespread public distrust in the legal and political systems. Rooted in philosophical nihilism, mainly as expounded by Friedrich Nietzsche, legal nihilism reflects the belief that law, much like other social constructs, lacks inherent purpose or justice. This phenomenon has grown due to disillusionment with political elites, legal bureaucracy, and corruption cases, leading the public to perceive legal enforcement as selective and biased. Public skepticism is exemplified by viral social media movements like #NoViralNoJustice, which suggest legal accountability only occurs when incidents gain online attention. This study examines the socio-legal implications of legal nihilism in Indonesia and its destructive effects on societal order. Drawing from legal philosophy and sociology, the paper analyzes how misaligned legal reforms, such as the controversial MyPertamina subsidy policy, deepen public dissatisfaction. The research highlights the urgent need for legal reforms prioritizing social welfare, transparency, and public trust, emphasizing the role of utilitarian legal philosophy as a potential framework for restoring legal credibility in Indonesia.